2005
DOI: 10.1021/bi0513251
|View full text |Cite
|
Sign up to set email alerts
|

A Ca2+/Calmodulin-Binding Peroxidase from Euphorbia Latex:  Novel Aspects of Calcium−Hydrogen Peroxide Cross-Talk in the Regulation of Plant Defenses,

Abstract: Calmodulin (CaM) is a ubiquitous Ca(2+) sensor found in all eukaryotes, where it participates in the regulation of diverse calcium-dependent physiological processes. In response to fluctuations of the intracellular concentration of Ca(2+), CaM binds to a set of unrelated target proteins and modulates their activity. In plants, a growing number of CaM-binding proteins have been identified that apparently do not have a counterpart in animals. Some of these plant-specific Ca(2+)/CaM-activated proteins are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Among plant Ca 2+ -sensing proteins, calmodulin (CaM) is increasingly appreciated as a critical player, but identifying its downstream target proteins and understanding their functions is still a work in progress. In this study, the authors isolated and sequenced the ELP cDNA and showed that the mature protein harbours two distinct CaM-binding sites (Mura et al, 2005). ELP-CaM interaction was also determined experimentally and by computer-assisted prediction methods.…”
Section: Defencementioning
confidence: 99%
“…Among plant Ca 2+ -sensing proteins, calmodulin (CaM) is increasingly appreciated as a critical player, but identifying its downstream target proteins and understanding their functions is still a work in progress. In this study, the authors isolated and sequenced the ELP cDNA and showed that the mature protein harbours two distinct CaM-binding sites (Mura et al, 2005). ELP-CaM interaction was also determined experimentally and by computer-assisted prediction methods.…”
Section: Defencementioning
confidence: 99%
“…Calcium is essential for horseraddish peroxidase (HRP) activity 16,17 and other peroxidases have been shown to bind Ca 2+ ions. 14,18 Some peroxidases even have a calmodulin binding domain 14,19 and calcium may switch a peroxidase between different modes of action. 20 In addition, apoplastic peroxidases are anchored in the cell wall matrix by calcium-dependent binding to pectate (i.e., polygalacturonic acid).…”
Section: Introductionmentioning
confidence: 99%
“…Since these peroxidases are dependent on calcium ions as well as on H 2 O 2 , they may function as indispensable nodes of a signaling network which employs these two known signaling molecules for stress defense. 19,30 In this study we have extracted peroxidases from a range of different plant sources and investigated their heat stability and dependency on calcium using a previously established in vitro assay. 31 We demonstrate that enzymes of similar function in plant species from natural habitats with varying maximum day temperatures exhibit different thermostability and different calcium responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Protein kinase C activity exhibits development-dependent modulation during seed maturation in sunflower. This has been observed both during early stages of embryo development and during the development of seeds by the use of PKC specific fluorescent probe Fim-1, a membrane permeant derivative of bisindoylmaleamide, as well as PKC inhibitors, namely staurosporine and bisindoylmaleamide.…”
mentioning
confidence: 99%